Chin imperfections: our experience with botulinum toxin A: Botulinum toxin in the chin - Corradino, Bartolo; Di Lorenzo, Sara; Corradino, Anna; Cascino, Andrea Pio (Aesthetic Medicine, 2023)
The chin is a highly complex structure from an anatomical and functional point of view, and the imperfections that arise are difficult to treat. We propose an innovative, infiltrative technique to correct the dimpling of the chin using botulinum toxin. The outcome of this procedure produced minimal side effects and optimal aesthetic results. The study consisted of 12 patients who were photographed before and after administering the botulinum toxin, and were asked to assess their degree of satisfaction of the final results. The satisfaction score was relatively high considering 100% of the patients reported as an adverse effect the loss of expressiveness, and each knew that they would have to repeat the procedure for a continued result.